THE USE OF COCONUT WATER FOR RAW MATERIAL OF VINEGAR - Hasanuddin Hasanuddin; Kurnia Herlina Dewi; Okta Wulandra (Jurnal Agroindustri, 2012)
Vinegar could be produced from any fruit juice. Coconut water as raw material was used by increasing sugar concentration. Vinegar is one of the alternatives in the use of coconut water waste. This is supported by the needs of the growing vinegar. Vinegar  manufacture involves two stages of fermentation (anaerobic and aerobic). Aerobic fermentation by adding yeast and sugar yield of 12% alcohol (the alcohol optimal), where as aerobic fermentation produces vinegar 4% -12.5% (SNI). The purpose of this study were to determine the optimal percentage of the addition of yeast and sugar to produce alcohol 12%, and to compare the quality of coco vinegar with SNI 01-3711-1995 vinegar. This study used factorial completely randomized design , the adding sugar and  yeast as treatment, 3 level of adding sugar and  yeast with 3 observations. Results of variance analysis  showed that the treatment was very real effect on levels of alcohol and alcohol pH. The Duncans Multiple Range Test (DMRT) showed that the highest quality levels of alcohol present in addition of 16% sugar and   6% of yeast. while the pH of alcohol contained in the addition of yeast 4.5% and sugar 10%